Occurrence and distribution of fresh-water molluscs in the Riacho Fundo Creek Basin, Brasilia, Brazil - Martins-Silva, Maria Júlia; Barros, Marilia (Revista de Biología Tropical, 2001)
To study the distribution of molluscs in the Riacho Fundo Creek (cerrado region of central Brazil), five creek sites were sampled once every two months for one year. Molluscs were sampled using standardized kick-net sampling. Four species of molluscs were found: Physella cubensis, Melanoides tuberculata, Biomphalaria straminea and Pisidium sp. The most abundant were P. cubensis and Pisidium sp. Physella cubensis was most abundant in the dry season and Pisidium sp. was most abundant in the rainy season, probably reflecting the rainy season increase of water currents